L’artisanat potier de grès et son implantation dans le Cher (xviie-milieu xixe siècle) : l’apport de la documentation écrite - Clément Rigault (Revue Archéologique du Centre de la France)
The knowledge of the stoneware pottery craft, in the Cher’s department, suffers from a lack of archaeological and bibliographic data, especially about the count and the location of workshops.However, diversity of varied archival sources brings to be possible the realization of an accurate mapping of pottery sites and clay extraction sites. The principal fact of the etude is the distribution of 85 workshops which are identified in the department. Especially the existence of two geographical centers presenting a similar structure with a specialized village concentrating pottery activity, and a significant number of workshops located on the fringes of this epicenter.This spatialization is also an opportunity to propose, using archaeological and geological data, groupings of workshops forming production areas.The main clay groups of these areas will be presented, in order to make easier a geographic identification of the archeological material. The emphasis is also placed on factors which played a role in the establishment and the development of these production areas.